Representasi Budaya dalam Film Berbagi Ruang Karya WWF-Indonesia dan Visinema Pictures - Salsabila, Sonia (Journal of Management, Education and Communication, 2023)
The film Sharing Space is a film that provides an overview of the culture of the Aceh Gayo people who live side by side with Sumatran elephants. This research discusses cultural representation in the film Sharing Space by WWF-Indonesia and Visinema Pictures. The aim of this research is to describe cultural representations in the film Sharing Space by WWF-Indonesia and Visinema Pictures. This research method uses media text analysis with a critical approach. The results of this research indicate that the cultural representation in the film Sharing Space is; 1). The efforts of the Aceh Gayo people to preserve their traditions. 2). The tradition of sharing in the life of the Aceh Gayo people. 3). Aceh Gayo people's concerns about living side by side with Sumatran elephants. 4). The traditions of the Aceh Gayo people in their efforts to survive.